Health Literacy and Refugee Women During the COVID-19 Pandemic: Outlooks for ESL Classes - Golesorkhi, Lara-Zuzan (Refuge: Canada’s Journal on Refugees, 2023)
During the COVID-19 pandemic, refugee women in the United States faced significant challenges to sustain their livelihoods, such as losing jobs and health care, becoming essential workers, and finding oneself again in unprecedented situations of limited mobility. These impacts reflect dynamics in migrant health literacy including language proficiency (skills-based approaches) as well as experiences, identities, and power relations in society (socio-cultural approaches). In this article, I explore these dynamics through a gender perspective with a focus on intra-familial health brokering, empowerment-based health education, and health information mapping by drawing on ethnographic research from Portland, Oregon. This includes interviews with 15 refugee women and representatives of organizations working in the context of migration as well as observations of service-providing community efforts. My interviews and observations demonstrate that disruptions in language learning, socio-cultural barriers, and limited access to health-related information resources have posed significant challenges to refugee women’s livelihoods during the pandemic. I suggest that English as a Second Language (ESL) classes can be imperative in addressing these challenges as the classes provide a space for language learning, intercultural dialogue, and information sharing in gender-responsive ways.